Pemeliharaan Jaringan Distribusi SUTM 20 kV (Penyulang Mawar) Di PT. PLN ULP Kampar: Maintenance Of 20 kV SUTM Distribution Network System (Rose Feeder) at PT. PLN ULP Kampar - Mugandi, Nabila Meitri (Institut Riset dan Publikasi Indonesia, 2022)
Distribution channel power distribution is commonly referred to as a 20 KV Medium Voltage Air Line (SUTM). The main problem that often experiences disturbances in the distribution network function is to deal with disturbances quickly and precisely, the most frequent disturbances experienced in the electric power system are in the distribution network such as disturbances due to lightning, wind, rain, animals and damage. This study aims to determine the disturbances in the 20 kV distribution network and how to maintain the 20 kV SUTM distribution network system in the rose feeder at PT. PLN (Persero) ULP Kampar which is currently being carried out. This research applies a preventive maintenance method known as ROW (Right Of Way) maintenance to increase the effectiveness of the 20 kV distribution network. The results showed that the disturbance was caused by internal factors such as disturbances in the SUTM channel and external factors caused by natural disasters, animals and kites. Preventive maintenance or ROW (Right Of Way) maintenance is implemented as an effort to increase the effectiveness of the distribution network such as felling tree branches that have hit the network, straightening sloping poles, cleaning broken wires, changing lightning arresters, and changing broken pins